Efficiency of low versus high airline pressure in stunning cattle with a pneumatically powered penetrating captive bolt gun - Octavio Oliveira, Steffan Edward [UNESP]; Gregory, Neville George; Dalla Costa, Filipe Antonio [UNESP]; Gibson, Troy John; Rodrigues Paranhos da Costa, Mateus Jose [UNESP] (Elsevier B.V., 2017)
The efficiency of stunning cattle was assessed in 443 animals (304 pure Zebu and 139 crossbred cattle), being mainly mature bulls and cows. Cattle were stunned using a Jarvis pneumatically powered penetrating captive bolt gun operating with low (160-175 psi, N = 82) and high (190 psi, N = 363) airline pressure, which was within the manufactures specifications. Signs of brain function and the position of the shots on the heads were recorded after stunning. Velocity of the captive bolt and its physical parameters were calculated. Cattle shot with low pressures showed more rhythmic respiration (27 vs. 8%, P < 0.001), less tongue protrusion (4 vs. 12%, P = 0.03) and less masseter relaxation (22 vs. 48%, P < 0.001). There was an increased frequency of shots in the ideal position when cattle were shot with the low compared to high airline pressures (15.3 vs. 3.1%). Bolt velocity and its physical parameters were significantly (P < 0.01) higher when using high pressure. Airline pressures below 190 psi are inappropriate when shooting adult Zebu beef cattle with pneumatically powered penetrating captive bolt guns.
Keywords: Airline pressure; Bolt velocity; Consciousness; Rhythmic respiration; Shot